Surface and interface analysis of electrochemically synthesized ferromagnetic/semiconducting Ni/GaAs(001) thin film. (4th June 2013) - Bhatt, Pramod; Bhatt, Ranu; Yusuf, S. M.
Abstract : Thin film of ferromagnetic (FM) metal (Ni) on a semiconducting substrate (GaAs), i.e. Ni/GaAs(001), has been synthesized using electrochemical method. The structural, chemical and magnetic properties at the surface and interface have been investigated using X‐ray diffraction (XRD)/grazing incidence X‐ray reflectivity (GIXRR), X‐ray photoelectron spectroscopy (XPS) and magneto‐optical Kerr effect (MOKE) techniques, respectively. A crystalline peak observed at 44.4º in the XRD pattern, corresponding to Ni(111) Bragg peak, confirms the monocrystalline nature of the film. The atomic force microscopy image shows small‐sized spherical crystallites uniformly deposited over the substrate. The fitted GIXRR pattern confirms a smooth Ni/GaAs(001) film surface with roughness of less than 5 ± 0.4 Å. The micro‐structural parameters, such as film thickness, surface and interface roughness, and electron density, are found to be 230 ± 5 Å, 4.5 ± 1 Å, 0.5 ± 0.02 Å and 6.38 ± 0.5 (Å −2 ), respectively. The chemical nature of the film at the surface and interface, investigated using a depth profile XPS technique, shows no diffusion of metallic Ga and As into Ni layer or vice versa, confirming a sharp FM/semiconducting Ni/GaAs(001) interface. The magnetization behavior investigated using MOKE technique at room temperature shows a soft FM nature of the film with coercivity of 75 Oe at the film surface. However, coercivity was found to be 35 Oe at the interface. In addition, the saturation magnetization is also found to decrease at the interface with decreasing Ni layer thickness. The observed magnetization behavior is correlated with structural and chemical changes that occur at the interface of Ni/GaAs(001) film. Copyright © 2013 John Wiley & Sons, Ltd.